Ketidakadilan Konstruksi Perempuan di Film dan Televisi - Siregar, Ashadi (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
In mediating relationship between individuals and the public, film and television present women in a particular form of social construction. On the one hand, they allow creative processes and expression of individual rights to take place, but on the other hand they reinforce the functioning of capitalistic and patriachical presentation of women. While film and television allow women to be focussed of interest, yet they take part in supperimpose structural injustice through commodification of women for satisficing the predominantly patriarchic mind.